Internalisasi Nilai Multikultural untuk Memperkokoh Toleransi Umat Kristen Dan Muslim Di Kota Kupang - Moses Kollo; Dixon Taek Bete (Mahesa Research Center, 2020)
This paper aims to describe (1) the causes of the emergence of religious multiculturalism (Christian and Muslim) in Kupang City; (2) How are the efforts of Christian and Muslim families in internalizing multicultural values to each child to strengthen tolerance between religious communities in Kupang City; and (3) what is the result of the merger of multicultural societies in Kupang City. This research is a qualitative descriptive study and focuses on the social interactions of the Christian and Muslim communities in Kupang City. Data were collected using interview techniques, observation and literature study then analyzed qualitatively which includes data reduction, data presentation and drawing conclusions. The results of this study conclude that (1) the emergence of religious multiculturalism (Christian and Muslim) is due to the fact that Kupang City is the center of government, economy, education for the people of NTT, and inter-religious and ethnic mixed marriages; (2) there are two steps by Christian and Muslim families in Kupang City in internalizing multicultural values to children, namely directly educating and practicing. First, educating, giving understanding to children to always have the spirit of mutual cooperation, communicative, tolerant, respect, respect and friendly to others; second, direct practice, namely being directly involved in social activities in the community such as celebrating joy and sorrow; and (3) “Beta Orang Kupang” is a new civilization that emerged as a result of the fusion of the people of Kota Kupang from various backgrounds